2021
DOI: 10.1038/s41598-021-88414-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cancer-derived EMT cells in the accumulation of 18F-fluorodeoxyglucose in the hypoxic cancer microenvironment

Abstract: A high rate of glycolysis, one of the most common features of cancer, is used in positron emission tomography (PET) imaging to visualize tumor tissues using 18F-fluorodeoxyglucose (18F-FDG). Heterogeneous intratumoral distribution of 18F-FDG in tissues has been established in some types of cancer, and the maximum standardized uptake value (SUVmax) has been correlated with poor prognosis. However, the phenotype of cells that show high 18F-FDG accumulation in tumors remains unknown. Here, we combined quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Both true and synthetic PET avid tumors demonstrated upregulated pathways involving EMT, hypoxia, and angiogenesis, corroborating the previous observations of high 18 F-labeled FDG activities in cancer cells undergoing EMT, particularly in hypoxic regions. 25 In addition, we observed that aggressive tumors with higher MTV, as stratified by true or synthetic PET, were consistently associated with elevated glycolytic activity and downregulated metabolism of fatty acid, bile acid, and heme. This is consistent with a recent study on The Cancer Genome Atlas lung adenocarcinomas showing that high glycolytic and low lipid metabolism exhibited high metastatic potency and poor survival.…”
Section: Discussionmentioning
confidence: 64%
“…Both true and synthetic PET avid tumors demonstrated upregulated pathways involving EMT, hypoxia, and angiogenesis, corroborating the previous observations of high 18 F-labeled FDG activities in cancer cells undergoing EMT, particularly in hypoxic regions. 25 In addition, we observed that aggressive tumors with higher MTV, as stratified by true or synthetic PET, were consistently associated with elevated glycolytic activity and downregulated metabolism of fatty acid, bile acid, and heme. This is consistent with a recent study on The Cancer Genome Atlas lung adenocarcinomas showing that high glycolytic and low lipid metabolism exhibited high metastatic potency and poor survival.…”
Section: Discussionmentioning
confidence: 64%
“…Several reports have shown that a high SUV in the malignant tumor correlates with the expression of speci c molecules, such as glucose transporter 1, Ki-67, hypoxia-induced factor-1α, and markers of the epithelial-mesenchymal transition. 19,20,21 Moreover, recent studies have demonstrated a correlation between SUV and forkhead box protein M1 expression, a downstream gene of the Wnt/β-catenin pathway, in breast cancer. 22 Activation of the Wnt/β-catenin signaling pathway has been reported to correlate with metastasis, 23 proliferation, 24 drug resistance, 25,26 and resistance to immune checkpoint inhibitor in many tumors, including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that a high SUV in the malignant tumor correlates with the expression of speci c molecules, such as glucose transporter 1, Ki-67, hypoxia-induced factor-1α, and markers of the epithelial-mesenchymal transition [19,20,21]. Moreover, recent studies have demonstrated a correlation between SUV and forkhead box protein M1 expression, a downstream gene of the Wnt/β-catenin pathway, in breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%